Understanding Mutual Funds Performance with mediation of Human Capital and GDP-Growth in Pakistan Mutual Funds: Demonstration of Structural Equation Model - Azam, Mohammad; Muhammad Arif (Journal of Social Sciences and Management Studies, 2024)
This work sheds light on the complex interplay between mutual fund performance, using human capital, and GDP growth as mediating variables in Pakistan through the lens of Structural Equation Modeling. By employing this sophisticated analytical approach, the findings uncovered nuanced nexus that traditional methods might have overlooked. The findings underscore the critical role of GDP-Growth and human capital as a mediating factor, suggesting that investments in mutual funds could have far-reaching effects on the financial performance on individual investors. Moreover, the demonstrated link between GDP-growth and mutual fund outcomes highlights the intricate web of economic factors influencing investment landscapes. Our findings thus reveal that the impact of the market factor and GDP growth on portfolio returns shows statistically significant estimates both mediation models. However, size-factor shows two portfolios significant while two portfolios insignificant results using both mediating variables. However, the value factor shows highly significant in both mediating models but reveal insignificant nexus with HC-Growth as mediating variable using only FF3FM. Moreover, momentum factor shows insignificant results for both mediating models. As Pakistan continues to develop its mutual fund market, policymakers and fund managers alike would do well to consider these interconnections in their decision-making processes.